2002
DOI: 10.1063/1.1469677
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effects in PbSe quantum wells

Abstract: In PbSe epitaxial thin films grown by thermal evaporation on KCl(001) substrates and covered with an EuS protective layer, oscillatory dependences of the galvanomagnetic and thermoelectric properties (electrical conductivity σ, the Hall coefficient RH, charge carrier mobility μ, and the Seebeck coefficient S) on the PbSe layer thickness d (3<d<200 nm) were observed at room temperature. Oscillations of the transport properties are associated with quantum size effects due to electron confinement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 35 publications
6
52
1
Order By: Relevance
“…But it should be noticed that experimental oscillation amplitudes in ddependences of thermoelectric parameters are much more large than the theoretical one. We consider that this difference has place because of assumption of infinite barrier height, what is confirmed by the data in [14], where for Te Eu PbTe/Pb x x 1− quantum wells it was found that energy barrier height reduction leads to increase of the thermoelectric power factor SP The authors [7,8] offer to determine a theoretical oscillation period value (ΔdB theor B ) for nanostructures, based on IV-VI compounds, using a known Fermi energy εB F B of single crystals. In our opinion, for nanostructures Fermi level is largely dependent on their topology and size, which, in turn, are determined by technological factors of growth.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…But it should be noticed that experimental oscillation amplitudes in ddependences of thermoelectric parameters are much more large than the theoretical one. We consider that this difference has place because of assumption of infinite barrier height, what is confirmed by the data in [14], where for Te Eu PbTe/Pb x x 1− quantum wells it was found that energy barrier height reduction leads to increase of the thermoelectric power factor SP The authors [7,8] offer to determine a theoretical oscillation period value (ΔdB theor B ) for nanostructures, based on IV-VI compounds, using a known Fermi energy εB F B of single crystals. In our opinion, for nanostructures Fermi level is largely dependent on their topology and size, which, in turn, are determined by technological factors of growth.…”
Section: Discussionsupporting
confidence: 70%
“…Naturally, we assumed that this behavior is due to size effects in quantum well formed by the potential barrier on the edge of polyamide substrate and oxidative layer on the condensate surface (similar to the results of [7][8][9][10]). …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier we reported oscillatory dependence of the transport properties on the layer thickness d in n-PbTe, n-PbSe, and n-PbS epitaxial thin films (see, for example, [17][18][19][20][21], and we attributed this oscillatory behavior to QSEs due to electron confinement in the IV-VI QWs. It is also of great interest to conduct similar studies for lead chalcogenides with p-type conductivity.…”
Section: Introductionmentioning
confidence: 90%
“…The quantum size effect leads the nanomaterials have very different magnetic, optical, acoustic, thermal, electrical and superconducting properties with conventional materials, such as very high non-linear optics, optical catalysis, high oxidability and reducibility etc. Due to quantum size effect, the galvanomagnetic and thermoelectric properties (electrical conductivity s, the Hall coefficient RH, charge carrier mobility m, and the Seebeck coefficient S) of nano-size PbSe thin film oscillate with the thin film thickness (3-200 nm) (Rogacheva et al, 2002). Silica glasses are doped with CdS and ZnS micro-crystals.…”
mentioning
confidence: 99%